2011
DOI: 10.4161/cc.10.11.15681
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K does not prevent soft tissue mineralization in a mouse model of pseudoxanthoma elasticum

Abstract: Pseudoxanthoma elasticum (PXE) is a heritable disease characterized by calcified elastic fibers in cutaneous, ocular and vascular tissues. PXE is caused by mutations in ABCC6, which encodes a protein of the ATP-driven organic anion transporter family. The inability of this transporter to secrete its substrate into the circulation is the likely cause of PXE. Vitamin K plays a role in the regulation of mineralization processes as a co-factor in the carboxylation of calcification inhibitors such as Matrix Gla Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 35 publications
(43 reference statements)
3
57
1
Order By: Relevance
“…Similar results were obtained in Abcc6 −/− mice (Li et al, 2013). However, ectopic mineralisation in Abcc6 −/− mice was not reduced by dietary administration of vitamin K 1 or K 2 (Brampton et al, 2011;Gorgels et al, 2011;Jiang et al, 2011) despite successfully raising the vitamin K concentration in tissues and serum; interestingly, this increase was significantly subdued in knockout mice and was accompanied by hepatic lesions, suggesting that Abcc6 −/− mice have an impaired ability to absorb, metabolise or distribute vitamin K (Brampton et al, 2011).…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar results were obtained in Abcc6 −/− mice (Li et al, 2013). However, ectopic mineralisation in Abcc6 −/− mice was not reduced by dietary administration of vitamin K 1 or K 2 (Brampton et al, 2011;Gorgels et al, 2011;Jiang et al, 2011) despite successfully raising the vitamin K concentration in tissues and serum; interestingly, this increase was significantly subdued in knockout mice and was accompanied by hepatic lesions, suggesting that Abcc6 −/− mice have an impaired ability to absorb, metabolise or distribute vitamin K (Brampton et al, 2011).…”
Section: Introductionsupporting
confidence: 72%
“…We propose that the reduced serum level of vitamin K seen in PXE patients is a consequence of its utilisation by GGCX in an attempt to restrict mineralisation, and not a consequence of the loss of ABCC6; subsequent administration of vitamin K could increase MGP carboxylation by GGCX, thus preventing hypermineralisation. This could also explain why Abcc6 −/− mice were more resistant to increases in serum levels caused by a vitamin K-rich diet (Brampton et al, 2011). One prediction of this model is that serum vitamin K would also be depleted in GACI patients (ENPP1…”
Section: Vitamin K Reduces Hypermineralisationmentioning
confidence: 99%
“…Vit K is a group of fat-soluble vitamins, which, in their reduced form, are needed for the posttranslational g-carboxylation of glutamic acid residues in proteins involved in blood coagulation and in the mineralization process (Booth, 2009). Interestingly, the low vit K concentrations measured in the circulation of PXE patients (Vanakker et al, 2010) were not associated by an impairment of their blood coagulation system, indicating that the vitamin can reach the liver to be metabolized and used for the activation of coagulation factors, whereas it seems to be extruded or transported less efficiently from hepatocytes to the periphery (Borst et al, 2008;Brampton et al, 2011), thus affecting connective tissues. In this scenario, it has been suggested that vit K supplementation might be capable of restoring MGP carboxylation and to inhibit ectopic calcifications (Borst et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…In this scenario, it has been suggested that vit K supplementation might be capable of restoring MGP carboxylation and to inhibit ectopic calcifications (Borst et al, 2008). However, recent studies in the PXE animal model (ABCC6 À / À mice) demonstrated that vit K supplementation does not counteract the mineralization of soft connective tissues (Brampton et al, 2011;Gorgels et al, 2011;Jiang et al, 2011). Key question is whether PXE fibroblasts are able to utilize vit K and restore an adequate MGP carboxylation.…”
Section: Introductionmentioning
confidence: 96%
“…In three separate animal studies, oral administration of high doses of vitamin K yielded elevated vitamin serum levels, but this elevation was insufficient to counteract ectopic mineralization in kidney arteries [51] and connective tissue surrounding the vibrissae of the Abcc6-deficient mouse [51][52][53]. These observations were affirmed by intravenous vitamin K administration in which vitamin K supply to peripheral tissue via the liver was bypassed, thus assuring that potentially defective hepatic Abcc6 protein did not affect vitamin K levels in peripheral tissues of Abcc6 −/− mice [52].…”
Section: Investigations Of Vitamin K and Adenosine As Candidate Abcc6 Smentioning
confidence: 99%